SHORT COMMUNICATION Modified Cognitive Remediation Therapy for Chronic Schizophrenia: An Outpatient Clinic Based Study - KUMAR MAHATO, AKASH (International Journal of Psychosocial Rehabilitation, 2020)
Cognitive remediation therapy (CRT) is an effective intervention for cognitive deficits in schizophrenia. The therapy often requires customization depending on the cognitive and socio-demographic profile of the client. The study describes a CRT module for chronic schizophrenia modified to be more inclusive of available resources, assistance of caregivers, and use of computer-based tasks and hypothesized to be effective in an outpatient setting. Five chronic patients with schizophrenia having impaired attention, memory, and executive functions underwent the modified CRT for a period of 6 months in an outpatient clinic and were followed up for one year. Improvement in the cognitive deficits as well as functional deficits in terms of disability level was found that were sustained in follow-up at 1 year. CRT gives ample scope of modification in outpatients and is effective in improving cognitive deficits in chronic patients with schizophrenia.